2020
DOI: 10.1021/acs.langmuir.0c02670
|View full text |Cite
|
Sign up to set email alerts
|

Unmodified Clay Nanosheets at the Air–Water Interface

Abstract: Quasi-two-dimensional (2D) nanolayers, such as graphene oxide or clay layers, adhere to gas–liquid or liquid–liquid interfaces. Particularly, clays are of wide general interest in this context because of their extensive and crucial use as Pickering emulsion stabilizers, as well as for their ability to provide colloidosome capsules. So far, clays could only be localized at oil–water or air–saline-water interfaces in aggregated states, while our results now show that clay nanosheets without any modification can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 91 publications
0
10
0
Order By: Relevance
“…Clay nanosheets are strong in-plane but rather soft cross-plane, allowing them to curve or undulate ( 46 , 51 ). Adjacent layers of clay nanosheets in the Bragg stacks that can be turbostratically stacked with random displacement ( 43 ). This will result in local variations of separations, while the moment of inertia of the clay layers is evenly spaced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clay nanosheets are strong in-plane but rather soft cross-plane, allowing them to curve or undulate ( 46 , 51 ). Adjacent layers of clay nanosheets in the Bragg stacks that can be turbostratically stacked with random displacement ( 43 ). This will result in local variations of separations, while the moment of inertia of the clay layers is evenly spaced.…”
Section: Resultsmentioning
confidence: 99%
“…Na-fluorohectorite (Na-FHt) is a synthetic clay mineral with superior quality regarding structural homogeneity, narrow charge distribution, and especially large aspect ratio (≈20,000) compared to most other clay minerals (41)(42)(43). Na-FHt when immersed in water forms nematic suspensions where single nanosheets are separated to uniform distances defined by the amount of water added (39,(43)(44)(45)(46), as evidenced by small-angle x-ray scattering (SAXS), birefringence (BF), or other methods (36,37,39,45,(47)(48)(49)(50).…”
Section: Introductionmentioning
confidence: 99%
“…They reported that high temperature and pressure were required as high-energy sources to separate the layers. Additionally, Akita and co-workers 22 and Brito et al 23 found that centrifugation and annealing processes were necessary to achieve a single-layered clay. Clearly, perfect exfoliation methods are poorly understood, although several mechanisms have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of a polymer nanocomposite largely depend on the properties of incorporated nanoparticles, namely, their shape, size, aspect ratio, specific surface area, and so on . Among all kinds of nanoparticles, clays have been found to be effective because of their wide availability, cost-effectiveness, and easy processability . In particular, the smectite-type clays are known to form nematic liquid-crystalline phases in aqueous suspensions. , Clay-based nanocomposites have been exceedingly studied and explored to find a wide range of applications, such as adsorbents of organic pollutants in water, soils, and air, rheological modifiers in paints, inks, and grease, and drug delivery carriers .…”
Section: Introductionmentioning
confidence: 99%